Swept-source optical coherence tomography and optical coherence tomography angiography in acquired toxoplasmic chorioretinitis: a case report - Diego Vezzola; Davide Allegrini; Alfredo Borgia; Paolo Fogagnolo; Luca Mario Rossetti; Mario R. Romano; Stefano De Cillà (Journal of Medical Case Reports, 2018)
Abstract Purpose To describe swept-source optical coherence tomography and optical coherence tomography angiography retinal changes in a case of acute toxoplasmic chorioretinitis both at the time of diagnosis and after healing. Case presentation A 57-year-old white woman suffering from acquired toxoplasmic chorioretinitis underwent swept-source optical coherence tomography and optical coherence tomography angiography both at the time of diagnosis and after healing. In the acute phase of the disease, swept-source optical coherence tomography clearly showed retinal and choroidal involvement in the superficial retina and in the choroidal swelling. Optical coherence tomography angiography showed a complete loss of deep and superficial capillary networks and of choroidal vessels in the area of the inflammation. After healing, swept-source optical coherence tomography showed a retinal thinning of the area involved, with a subversion of retinal layers and no visible change at the choroid level. On the other hand, optical coherence tomography angiography showed the persistence of a vascular occlusion at the retina and choroid level. Conclusion This is the first case in the optical coherence tomography angiography literature that shows the imaging of toxoplasmic chorioretinal lesions. This case confirms the involvement of the retina and choroid in toxoplasmic uveitis and the disruptive potential of such inflammation. The optical coherence tomography angiography performed after healing showed a persistent ablation of the retina, choriocapillaris, and choroidal vessels. The non-invasive optical coherence tomography angiography imaging technique may have diagnostic and prognostic value in regard to toxoplasmic uveitis.